2005
DOI: 10.1246/cl.2005.822
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Ba5Ta4O15 to Decomposition of H2O into H2 and O2

Abstract: The photocatalytic performance of barium tantalates in the decomposition of H2O into H2 and O2 was investigated. Ba5Ta4O15 that was prepared under Ta rich atmosphere exhibited remarkable photocatalytic activity. Under the same reaction conditions, its activity was the highest among all of the alkali earth-tantalum mixed-oxide photocatalysts prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…The preferable state of Zn added Ga 2 O 3 photocatalyst contains 1 atomic % of Zn ion and obtained by calcining at around 1,223 K. The photocatalytic activity of H 2 O splitting over Ni(1 wt%)/ Zn(1 atom %)--Ga 2 O 3 is 4,100 lmol/h for H 2 and 2,200 lmol/h for O 2 production, respectively. In order to evaluate the photocatalytic activity, the photocatalytic activity of NiO supported Tantalate photocatalysts, which carried out nearly the same photo-reaction system, were investigated from previous reports [1,2,[14][15][16]. It was confirmed that the photocatalytic activity of Ni/Zn-Ga 2 O 3 exhibited the same extent as alkali or alkali earth tantalum mixed oxide photocatalysts.…”
Section: Resultsmentioning
confidence: 89%
“…The preferable state of Zn added Ga 2 O 3 photocatalyst contains 1 atomic % of Zn ion and obtained by calcining at around 1,223 K. The photocatalytic activity of H 2 O splitting over Ni(1 wt%)/ Zn(1 atom %)--Ga 2 O 3 is 4,100 lmol/h for H 2 and 2,200 lmol/h for O 2 production, respectively. In order to evaluate the photocatalytic activity, the photocatalytic activity of NiO supported Tantalate photocatalysts, which carried out nearly the same photo-reaction system, were investigated from previous reports [1,2,[14][15][16]. It was confirmed that the photocatalytic activity of Ni/Zn-Ga 2 O 3 exhibited the same extent as alkali or alkali earth tantalum mixed oxide photocatalysts.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Sr 2 Nb 2 O 7 (4.0 eV) and Sr 2 Ta 2 O 7 (4.6 eV), [21][22][23] La 3 NbO 7 (3.9 eV) and La 3 TaO 7 (4.6 eV), [24,25] Rb 4 Nb 6 O 17 (3.4 eV) and Rb 4 Ta 6 O 17 (4.2 eV), [26] [27][28][29] have been reported as highly active photocatalysts for water splitting. However, the band gaps of these niobate photocatalysts are so wide, except for Rb 4 Nb 6 O 17 , because the energy structures of these photocatalysts localize, more or less, due to large distortion of a framework of a crystal structure or decreasing of structural three-dimensionality as discussed in the previous paper.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, new photocatalysts consisting of metal ions with d 0 and d 10 electron configurations have been developed for photocatalytic H 2 and O 2 evolution from water under UV irradiation, one after another. [1][2][3][4][5][6][7][8][9][10] have been also reported as photocatalysts. Especially, the GaN:ZnO photocatalyst is active for water splitting into H 2 and O 2 .…”
mentioning
confidence: 99%